Sodium-ion battery conductive agent and preparation method thereof

Through the composite of hyperbranched polymer and carbon-based conductive material, the problems of insufficient conductivity and poor dispersion of sodium ion battery conductive agent are solved, and efficient charging and good cycle performance of the battery are achieved.

CN120280492AActive Publication Date: 2025-07-08SHANGHAI XUANDIAN NEW MATERIALS CO LTD

Patent Information

Application Number
CN202510424046.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-07-08
Estimated Expiration
2045-04-07

AI Technical Summary

Technical Problem

The existing sodium ion battery conductive agents have problems such as insufficient conductivity, poor dispersion, easy agglomeration and high preparation costs, which affect the electrochemical performance of the battery.

Method used

Hyperbranched polymers and carbon-based conductive materials are combined to prepare hyperbranched polymers through specific chemical reactions, and a multi-path transmission channel is formed by combining carbon-based conductive materials to improve the charging specific capacity and cycling performance of the battery.

Benefits of technology

It significantly enhances the conjugation effect and electron transmission efficiency of the conductive agent, improves the battery's charging specific capacity, first-time Coulomb efficiency and cycling performance, reduces irreversible capacity loss, and extends the battery's cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120280492A_ABST
    Figure CN120280492A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery conductive agent and a preparation method thereof, and belongs to the technical field of sodium ion batteries. The sodium ion battery conductive agent comprises a hyperbranched polymer and a carbon-based conductive material, the hyperbranched polymer catalyzes 2-thiophenecarbonitrile through trifluoromethanesulfonic acid to generate 2, 4, 6-tri (2-thienyl)-1, 3, 5-triazine through polymerization, then aldehyde groups are introduced to prepare thienyl triazinyl formaldehyde, and the thienyl triazinyl formaldehyde reacts with 2, 4, 6-tri (4-aminophenyl)-1, 3, 5-triazine to prepare the sodium ion battery conductive agent. A triazine structure in the hyperbranched polymer in the conductive agent prepared by the invention is cooperated with a thiophene unit, so that the conjugation effect and the electron transmission efficiency can be remarkably enhanced; the flexible and hyperbranched structure of the thiophene ring can buffer volume expansion in the charging and discharging process, and the cycle performance is prolonged; the hyperbranched polymer can be effectively cross-linked with the carbon-based conductive material to form a multi-path transmission channel, so that the charging specific capacity of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium-ion batteries, and specifically relates to a conductive agent for sodium-ion batteries and a preparation method thereof. Background Art

[0002] Due to the abundant energy storage of sodium resources, sodium-ion batteries have greater cost advantages compared to lithium-ion batteries and have good development prospects, attracting more and more attention. Currently, higher requirements are put forward for the electrical conductivity and cycle stability of electrode materials used in sodium-ion batteries. Therefore, it is necessary to add a conductive agent to improve the conductivity. As the core material for improving the electrode conductivity of sodium-ion batteries, commonly used ones include conductive carbon black, carbon fiber, carbon nanotubes, and graphene, etc. Conductive carbon black has low conductivity and requires a high addition amount to construct a continuous conductive network. Moreover, it has a relatively large specific surface area, poor dispersibility in the slurry, and is prone to agglomeration; the surface of carbon fiber is smooth and lacks active sites, resulting in a weak binding force with the electrode material and a high contact resistance; the addition amount of graphene has a great influence on its conductive effect. When the addition amount is small, the sheet structure of graphene makes it have a more developed conductive network, but its preparation cost is high, it is difficult to disperse, and it reduces the ionic conductivity of the electrode sheet; the linear structure of carbon nanotubes with a small diameter and a large aspect ratio makes it extremely prone to agglomeration, resulting in a significant decline in the electrochemical performance of the battery.

[0003] Chinese Patent No. CN117691116A discloses a conductive agent for the negative electrode of a sodium-ion battery and a sodium-ion battery. By adding PEDOT nanowires, the mechanical properties and cycle performance of the negative electrode of the sodium-ion battery can be significantly improved. However, PEDOT nanowires have a small diameter and a large aspect ratio, and are prone to agglomeration, which affects their conductive performance. Summary of the Invention

[0004] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide a conductive agent for sodium-ion batteries and a preparation method thereof.

[0005] To achieve the above purpose, the present invention is realized through the following technical solutions:

[0006] A conductive agent for sodium-ion batteries, comprising a hyperbranched polymer and a carbon-based conductive material;

[0007] Wherein, the hyperbranched polymer is prepared by polymerizing 2-thiophenecarbonitrile with trifluoromethanesulfonic acid to generate 2,4,6-tris(2-thienyl)-1,3,5-triazine, then introducing an aldehyde group to obtain thiophene-based triazine-based formaldehyde, and then reacting with 2,4,6-tris(4-aminophenyl)-1,3,5-triazine.

[0008] The hyperbranched polymer is prepared by the following method:

[0009] S1: Under ice bath, slowly add 2-thiophenecarbonitrile to a chloroform solution of trifluoromethanesulfonic acid, stir for 0.5 - 1.5 h, raise the temperature to room temperature and react for 20 - 26 h. After post-treatment, 2,4,6-tris(2-thienyl)-1,3,5-triazine is obtained. The reaction equation is shown as follows:

[0010]

[0011] S2: Mix 2,4,6-tris(2-thienyl)-1,3,5-triazine with DMF, add phosphorus oxychloride dropwise, raise the temperature to 70 - 90 °C, keep warm for 2 - 5 h. After post-treatment, thiophene-based triazinecarbaldehyde is obtained. The reaction equation is shown as follows:

[0012]

[0013] S3: Under nitrogen protection, add 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and thiophene-based triazinecarbaldehyde to a mixed solution of glacial acetic acid, water and DMA, raise the temperature to 100 - 130 °C, react for 36 - 48 h. After post-treatment, a hyperbranched polymer is obtained. The reaction equation is shown as follows:

[0014]

[0015] It should be noted that the structural formula of the above hyperbranched polymer is only used to represent the reaction between functional groups in this step.

[0016] In step S1, the molar ratio of trifluoromethanesulfonic acid to 2-thiophenecarbonitrile in the feed is 1:(8 - 12).

[0017] In step S2, the mass ratio of 2,4,6-tris(2-thienyl)-1,3,5-triazine, DMF, and phosphorus oxychloride in the feed is 1:(8 - 10):(0.2 - 0.6).

[0018] In step S3, the molar ratio of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to thiophene-based triazinecarbaldehyde in the feed is (0.8 - 1.2):0.5.

[0019] In step S3, the volume ratio of glacial acetic acid, water and DMA in the mixture is 1:(2.5 - 4):(5 - 6).

[0020] The carbon-based conductive material is prepared by the following method:

[0021] Dissolve nickel nitrate, trimesic acid and polyvinylpyrrolidone in a mixed solution of DMF and deionized water. Under closed conditions, raise the temperature to 140 - 160 °C and react for 8 - 12 h. After post-treatment, a carbon-based conductive material is obtained.

[0022] The mass ratio of the hyperbranched polymer to the carbon-based conductive material is (3 - 6):1.

[0023] A preparation method of a sodium ion battery conductive agent includes the following steps:

[0024] S1: Weigh by weight: 3 - 6 parts of hyperbranched polymer, 1 part of carbon-based conductive material, and 50 - 70 parts of deionized water;

[0025] S2: Add each component into a reaction flask, stir for 2 h to disperse evenly, filter, and dry at 60 - 70 °C for 10 h to obtain the sodium ion battery conductive agent.

[0026] Due to the above technical solutions, the beneficial effects of the present invention include:

[0027] (1) In the conductive agent prepared by the present invention, the triazine structure in the hyperbranched polymer synergistically with the thiophene unit can significantly enhance the conjugation effect and electron transport efficiency; the flexibility of the thiophene ring and the hyperbranched structure can buffer the volume expansion during charge and discharge, and prolong the cycle performance; the high chemical stability of the triazine backbone can reduce the irreversible capacity loss in the first cycle.

[0028] (2) In the conductive agent prepared by the present invention, the hyperbranched polymer can effectively crosslink with the carbon-based conductive material to form a multi-path transmission channel, improving the charge specific capacity of the battery. Description of the Drawings

[0029] Figure 1 SEM image of the lychee-like carbon-based conductive material prepared in Example 4. Detailed Embodiments

[0030] The following is further illustrated with reference to embodiments, but the present invention is not limited to these embodiments.

[0031] Example 1 Preparation of Hyperbranched Polymer:

[0032] S1: Under ice bath, stir and mix 0.1 mol of trifluoromethanesulfonic acid and 800 ml of chloroform evenly, slowly dropwise add 0.8 mol of 2-thiophenecarbonitrile, finish dropping in 1 h, stir for 0.5 h, raise the temperature to room temperature and react for 26 h, add 500 ml of 5 wt% ammonia water solution, stir for 15 min, separate the organic layer, extract the water layer with 200 ml of chloroform, combine the organic layers, dry with 30 g of anhydrous magnesium sulfate, filter, and perform reduced pressure distillation at 45 °C for 3 h to obtain 2,4,6-tris(2-thienyl)-1,3,5-triazine;

[0033] S2: Put 100 g of 2,4,6-tris(2-thienyl)-1,3,5-triazine and 800 g of DMF into a reaction flask, add 20 g of phosphorus oxychloride dropwise, finish dropping in 30 min, raise the temperature to 70 °C, keep warm for 5 h, cool to room temperature, add 500 ml of ice water, adjust the pH to 7 with 30 wt% sodium hydroxide solution, separate the layers, wash the organic phase with deionized water (300 ml × 2 times), distill the organic phase under reduced pressure at 60 °C for 3 h, and dry it in vacuum at 80 °C for 10 h to obtain thienyltriazinyl formaldehyde;

[0034] S3: Under nitrogen protection, put 100 ml of glacial acetic acid, 250 ml of water, 600 ml of DMA (N,N-dimethylacetamide), 0.8 mol of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, and 0.5 mol of thienyltriazinyl formaldehyde into a reaction flask in sequence, raise the temperature to 100 °C, react for 48 h, cool to room temperature, filter, wash with 300 ml of methanol and 300 ml of THF in sequence, and dry it in vacuum at 80 °C for 10 h to obtain a hyperbranched polymer.

[0035] Example 2 Preparation of hyperbranched polymer:

[0036] S1: Under ice bath, stir and mix 0.1 mol of trifluoromethanesulfonic acid and 800 ml of chloroform evenly, slowly add 1 mol of 2-thiophenecarbonitrile dropwise, finish dropping in 1 h, stir for 1 h, raise the temperature to room temperature and react for 24 h, add 500 ml of 5 wt% ammonia water solution, stir for 15 min, separate the organic layer, extract the aqueous layer with 200 ml of chloroform, combine the organic layers, dry with 30 g of anhydrous magnesium sulfate, filter, distill under reduced pressure at 45 °C for 3 h to obtain 2,4,6-tris(2-thienyl)-1,3,5-triazine;

[0037] S2: Put 100 g of 2,4,6-tris(2-thienyl)-1,3,5-triazine and 900 g of DMF into a reaction flask, add 50 g of phosphorus oxychloride dropwise, finish dropping in 30 min, raise the temperature to 80 °C, keep warm for 4 h, cool to room temperature, add 500 ml of ice water, adjust the pH to 7 with 30 wt% sodium hydroxide solution, separate the layers, wash the organic phase with deionized water (300 ml × 2 times), distill the organic phase under reduced pressure at 60 °C for 3 h, and dry it in vacuum at 80 °C for 10 h to obtain thienyltriazinyl formaldehyde;

[0038] S3: Under nitrogen protection, put 100 ml of glacial acetic acid, 300 ml of water, 540 ml of DMA, 1.1 mol of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, and 0.5 mol of thienyltriazinyl formaldehyde into a reaction flask in sequence, raise the temperature to 120 °C, react for 46 h, cool to room temperature, filter, wash with 300 ml of methanol and 300 ml of THF in sequence, and dry it in vacuum at 80 °C for 10 h to obtain a hyperbranched polymer.

[0039] Example 3 Preparation of hyperbranched polymer:

[0040] S1: Under an ice bath, 0.1 mol of trifluoromethanesulfonic acid and 800 ml of chloroform were stirred and mixed evenly, and 1.2 mol of 2-thiophenecarbonitrile was slowly added dropwise. The addition was completed in 1 h, and the mixture was stirred for 1.5 h. Then it was warmed to room temperature and reacted for 20 h. 500 ml of 5 wt% aqueous ammonia solution was added, and the mixture was stirred for 15 min. The organic layer was separated, the aqueous layer was extracted with 200 ml of chloroform, the organic layers were combined, dried with 30 g of anhydrous magnesium sulfate, filtered, and distilled under reduced pressure at 45 °C for 3 h to obtain 2,4,6-tris(2-thienyl)-1,3,5-triazine;

[0041] S2: 100 g of 2,4,6-tris(2-thienyl)-1,3,5-triazine and 1000 g of DMF were placed in a reaction flask, and 60 g of phosphorus oxychloride was added dropwise. The addition was completed in 30 min, the temperature was raised to 90 °C, and the mixture was kept warm for 2 h. Then it was cooled to room temperature, 500 ml of ice water was added, and the pH was adjusted to neutral with 30 wt% sodium hydroxide solution. After layering, the organic phase was washed with deionized water (300 ml × 2 times), the organic phase was distilled under reduced pressure at 60 °C for 3 h, and vacuum dried at 80 °C for 10 h to obtain thiophene-based triazine-based formaldehyde;

[0042] S3: Under nitrogen protection, 100 ml of glacial acetic acid, 400 ml of water, 500 ml of DMA, 1.2 mol of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, and 0.5 mol of thiophene-based triazine-based formaldehyde were successively placed in a reaction flask. The temperature was raised to 130 °C and reacted for 36 h. Then it was cooled to room temperature, filtered, washed successively with 300 ml of methanol and 300 ml of THF, and vacuum dried at 80 °C for 10 h to obtain a hyperbranched polymer.

[0043] Example 4 Preparation of carbon-based conductive material:

[0044] 160 g of DMF, 80 g of deionized water, 30 g of nickel nitrate, 10 g of trimesic acid, and 90 g of polyvinylpyrrolidone were successively added to a reaction flask. After stirring for 1 h, under a closed condition, the temperature was raised to 150 °C and reacted for 10 h. Then it was cooled to room temperature, filtered, washed with 300 ml of ethanol, and vacuum dried at 60 °C for 8 h to obtain a solid, which was calcined at 500 °C for 3 h to obtain a carbon-based conductive material.

[0045] Example 5 Preparation of conductive agent:

[0046] S1: Weigh by weight: 3 g of hyperbranched polymer (prepared in Example 1), 1 g of carbon-based conductive material (prepared in Example 4), and 50 g of deionized water;

[0047] S2: Add each component to a reaction flask, stir for 2 h to disperse evenly, filter, and dry at 60 °C for 10 h to obtain a conductive agent for sodium-ion batteries.

[0048] Example 6 Preparation of Conductive Agent

[0049] S1: Weigh by weight: 5 g of hyperbranched polymer (prepared in Example 2), 1 g of carbon-based conductive material (prepared in Example 4), and 60 g of deionized water;

[0050] S2: Add each component into a reaction flask, stir for 3 h to disperse evenly, filter, and dry at 60 °C for 10 h to obtain a conductive agent for sodium-ion batteries.

[0051] Example 7 Preparation of Conductive Agent

[0052] S1: Weigh by weight: 6 g of hyperbranched polymer (prepared in Example 3), 1 g of carbon-based conductive material (prepared in Example 4), and 70 g of deionized water;

[0053] S2: Add each component into a reaction flask, stir for 2 h to disperse evenly, filter, and dry at 70 °C for 10 h to obtain a conductive agent for sodium-ion batteries.

[0054] Comparative Example 1

[0055] A conductive agent for sodium-ion batteries, the preparation method of which is basically the same as that of Example 6, the difference is that no carbon-based conductive material is added.

[0056] Comparative Example 2

[0057] A conductive agent for sodium-ion batteries, the preparation method of which is basically the same as that of Example 6, the difference is that the hyperbranched polymer is replaced by a hyperbranched polymer prepared by the following method:

[0058] Under nitrogen protection, 100 ml of glacial acetic acid, 300 ml of water, 540 ml of DMA, 1.1 mol of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, and 0.5 mol of benzene-1,3,5-tricarbaldehyde were successively placed in a reaction flask, heated to 120 °C, reacted for 46 h, cooled to room temperature, filtered, washed successively with 300 ml of methanol and 300 ml of THF, and dried in vacuum at 80 °C for 10 h to obtain a hyperbranched polymer.

[0059] Comparative Example 3

[0060] A conductive agent for sodium-ion batteries, the preparation method of which is basically the same as that of Example 6, the difference is that the hyperbranched polymer is replaced by a hyperbranched polymer prepared by the following method:

[0061] Under nitrogen protection, 100 ml of glacial acetic acid, 300 ml of water, 540 ml of DMA, 1.1 mol of 4,4',4"-triaminotriphenylmethane, and 0.5 mol of thienyltriazinyl formaldehyde (prepared in Example 2) were sequentially placed into a reaction flask, heated to 120 °C, reacted for 46 h, cooled to room temperature, filtered, washed successively with 300 ml of methanol and 300 ml of THF, and dried in vacuo at 80 °C for 10 h to obtain a hyperbranched polymer.

[0062] Comparative Example 4

[0063] A sodium-ion battery conductive agent, the preparation method of which is basically the same as that of Example 6, except that the hyperbranched polymer is replaced by a hyperbranched polymer prepared by the following method:

[0064] The preparation method of the hyperbranched polymer is basically the same as that of Example 2, except that 2-thiophenecarbonitrile in step S1 is replaced by an equimolar amount of 2-thiopheneacetonitrile.

[0065] The conductive agents of Examples 5-7 and the comparative examples were applied to sodium-ion batteries, and the sodium-ion batteries were prepared by the following process:

[0066] (1) Preparation of the positive electrode sheet of the sodium-ion battery: Na 0.7 MnO2: binder (PVDF): conductive agent were uniformly mixed at a mass ratio of 90:5:5, a total of 10 g, 15 ml of N-methylpyrrolidone was added and stirred evenly to obtain a positive electrode slurry, which was uniformly coated on the surface of aluminum foil (coating thickness 200 μm), dried in vacuo at 100 °C for 10 h, and compacted and cut under a pressure of 3 MPa by a roller machine to obtain a positive electrode sheet with a diameter of 12 mm;

[0067] (2) Preparation of the negative electrode sheet: 0.5 g of thickener CMC (Daicel CMC2200, Japan) was stirred evenly with 10 g of deionized water, 9 g of hard carbon (Kuraray, Japan) was added and mixed evenly, 0.5 g of binder SBR (BASF Styrofan 7212) was added, and after stirring evenly, a negative electrode slurry was obtained, which was uniformly coated on the surface of aluminum foil (coating thickness 200 μm), dried in vacuo at 100 °C for 10 h, and compacted and cut under a pressure of 3 MPa by a roller machine to obtain a negative electrode sheet with a diameter of 12 mm;

[0068] Electrolyte preparation: 25 ml of ethylene carbonate and 25 ml of dimethyl carbonate were mixed evenly. In an argon glove box, 3 g of NaPF6 was slowly added to the mixed solvent and stirred until completely dissolved.

[0069] Sodium-ion battery assembly: The positive electrode sheet, negative electrode sheet and separator (glass fiber separator) are wound together in a square winding manner to form a pole group, which is then placed into a battery case (formed by aluminum-plastic packaging film). They are stacked in the order of "positive electrode - separator - negative electrode", placed into an aluminum-plastic film packaging bag, leaving an injection port, injecting electrolyte, standing for 24 h for infiltration, and then vacuum heat-sealing.

[0070] The binder (PVDF) used in this application has a grade of FL2300 PVDF, purchased from Zhejiang Funolin Chemical New Materials Co., Ltd.

[0071] The conductive agents prepared in the examples and comparative examples are assembled into sodium-ion batteries for electrical performance testing. After all the electrochemical performance tests are assembled, they are left standing for 24 h and then carried out at a constant temperature of 25 °C. The battery is charged at a constant current density of 0.1C to 4.2V, and left standing for 5 min; then charged at a constant voltage for 30 min and left standing for 5 min; then the battery is discharged at a constant current to 2.5V using the same current density for the first charge-discharge test; a 1C rate is selected to test the cycle performance of the battery, and the cycle period is 100 times, and the test temperature is 25 °C. The test results are shown in Table 1.

[0072] Table 1 Performance determination of sodium-ion batteries assembled with the conductive agents prepared in the examples and comparative examples

[0073]

[0074]

[0075] It can be seen from Examples 5, 6, and 7 in Table 1 that the sodium-ion batteries assembled with the conductive agents prepared in the present invention have good charge specific capacity, initial Coulomb efficiency, and cycle performance.

[0076] Comparative Example 1 uses only hyperbranched polymer as the conductive agent, and its electrical performance is much lower than that of the conductive agent prepared in the example. The reason is that: the lack of a highly conductive network of carbon materials leads to low electron transfer efficiency and poor electrode structure stability.

[0077] Comparative Example 2 is a comparative example different from Example 7. The difference is that the hyperbranched polymer is replaced with a hyperbranched polymer synthesized from mellitic aldehyde and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine. Its electrochemical performance is poor. The reason is that the reduction of triazine and thiophene rings weakens the conjugation effect, and the replacement of the flexible thiophene ring with a rigid benzene ring reduces the ability to buffer volume expansion, resulting in a decrease in the initial Coulomb efficiency and capacity retention rate.

[0078] The conductive agent in Comparative Example 3 lacks a triazine skeleton connected to the benzene ring in the hyperbranched polymer. The absence of the triazine skeleton reduces the molecular conjugation and chemical stability, affecting the electron transfer efficiency and cycle stability.

[0079] The reason for the poor electrochemical performance of Comparative Example 4 is as follows: for the hyperbranched polymer prepared from 2-thiophenecarbonitrile, the thiophene group is directly connected to the triazine ring through a single bond, forming a relatively large conjugated system, which is conducive to electron delocalization and improves the conductivity and charge transport efficiency of the material. For the hyperbranched polymer prepared from 2-thiopheneacetonitrile, the thiophene group is connected to the triazine ring through a methylene group (-CH2-), resulting in the interruption of conjugation and the obstruction of the electron transport path, thereby affecting the rate performance and cycle stability of the battery.

[0080] In summary, the conductive agent prepared by the present invention has good charge specific capacity for the following reasons: the D-A (donor-acceptor) structure of the triazine-thiophene hyperbranched polymer can significantly enhance the conjugation effect and electron transport efficiency; after the hyperbranched polymer is compounded with the carbon-based material, its high specific surface area and conductive network improve the conductivity and the transport rate of sodium ions, thereby increasing the charge specific capacity of the material. The good initial coulombic efficiency stems from the high chemical stability of the triazine backbone, which can reduce the irreversible capacity loss in the first cycle. The good cycle performance is due to the flexibility of the thiophene ring and the three-dimensional network of the hyperbranched polymer, which can buffer the volume expansion during charge and discharge, inhibit the structural collapse, and prolong the cycle life.

[0081] The above are only the preferred embodiments of the present invention and are not used to limit the present invention; however, for those of ordinary skill in the art, without departing from the scope of the technical solution of the present invention, any minor changes, modifications, and equivalent variations made using the technical content disclosed above are all equivalent embodiments of the present invention; at the same time, any equivalent changes, modifications, and variations made to the above embodiments based on the essence of the present invention still fall within the protection scope of the technical solution of the present invention.

Claims

1. A sodium-ion battery conductive agent, characterized in that, It includes a hyperbranched polymer and a carbon-based conductive material; Among them, the hyperbranched polymer is prepared by polymerizing 2-thiophenecarbonitrile with trifluoromethanesulfonic acid catalysis to generate 2,4,6-tris(2-thienyl)-1,3,5-triazine, then introducing an aldehyde group to obtain thiophene-based triazine-based formaldehyde, and then reacting with 2,4,6-tris(4-aminophenyl)-1,3,5-triazine.

2. The conductive agent for a sodium ion battery according to claim 1, wherein The hyperbranched polymer is prepared by the following method: S1: Under ice bath, slowly drop 2-thiophenecarbonitrile into a chloroform solution of trifluoromethanesulfonic acid, stir for 0.5 - 1.5 h, raise the temperature to room temperature and react for 20 - 26 h, and perform post-treatment to obtain 2,4,6-tris(2-thienyl)-1,3,5-triazine; S2: Mix 2,4,6-tris(2-thienyl)-1,3,5-triazine with DMF, drop phosphorus oxychloride, raise the temperature to 70 - 90 °C, keep warm for 2 - 5 h, and perform post-treatment to obtain thiophene-based triazine-based formaldehyde; S3: Under nitrogen protection, add 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and thiophene-based triazine-based formaldehyde to a mixed solution of glacial acetic acid, water and DMA, raise the temperature to 100 - 130 °C, react for 36 - 48 h, and perform post-treatment to obtain the hyperbranched polymer.

3. The conductive agent for a sodium ion battery according to claim 2, wherein In step S1, the molar ratio of trifluoromethanesulfonic acid to 2-thiophenecarbonitrile in the feed is 1:(8 - 12).

4. The conductive agent for a sodium ion battery according to claim 2, wherein, In step S2, the mass ratio of 2,4,6-tris(2-thienyl)-1,3,5-triazine, DMF, and phosphorus oxychloride in the feed is 1:(8 - 10):(0.2 - 0.6).

5. A sodium ion battery conductive agent according to claim 2, characterized in that, In step S3, the molar ratio of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to thiophene-based triazine-based formaldehyde in the feed is (0.8 - 1.2):0.

5.

6. The conductive agent for a sodium ion battery according to claim 2, wherein In step S3, the volume ratio of glacial acetic acid, water and DMA in the mixture is 1:(2.5 - 4):(5 - 6).

7. The conductive agent for a sodium ion battery according to claim 1, wherein The carbon-based conductive material is prepared by the following method: Dissolve nickel nitrate, trimellitic acid and polyvinylpyrrolidone in a mixed solution of DMF and deionized water, and under sealed conditions, raise the temperature to 140 - 160 °C and react for 8 - 12 h, and perform post-treatment to obtain the carbon-based conductive material.

8. The conductive agent for a sodium-ion battery according to claim 1, wherein The mass ratio of the hyperbranched polymer to the carbon-based conductive material in the feed is (3 - 6):

1.

9. A method for preparing a sodium ion battery conductive agent according to any one of claims 1-8, characterized in that, It includes the following steps: S1: Weigh by weight: 3 - 6 parts of hyperbranched polymer, 1 part of carbon-based conductive material, and 50 - 70 parts of deionized water; S2: Add each component into a reaction flask, stir for 2 - 4 h, disperse evenly, filter, and dry at 60 - 70 °C for 10 h to obtain a sodium-ion battery conductive agent.

Citation Information

Patent Citations

  • Triazine type photonic functional material and preparation and application method thereof

    CN101717396A

  • Method of producing triazine ring-containing hyperbranched polymer

    JP2014098101A

  • Conjugated Thiophenes Having Conducting Properties and Synthesis of Same

    US20070287842A1

Cited By

  • Sterilization composition containing origanum vulgare and preparation method thereof

    CN121041187A